Visual hermeneutics as a tool to introduce empathy and core physician attributes in doctor-patient relationship for first-year medical undergraduate students - Sushma Prabhath; Uma Kulkarni; Vani Lakshmi R.; Bikash Patra; Eshwari K.; Divya Arvind Prabhu; Kirtana R. Nayak (BMC Medical Education)
Abstract Background The doctor-patient relationship is essential for effective patient care, yet medical education often neglects to nurture the quality such as empathy during the initial years of training. Doctor-patient relationship is one of the modules taught in first year as part of mandatory AETCOM (Attitude, Ethics, and Communication) course in the undergraduate Indian medical curriculum. Hermeneutics, a method of interpretation, can play a vital role in introducing observational and reflective thinking skills. This study aimed to introduce empathy concepts and attributes of a good physician to first-year medical students through the use of paintings and visual hermeneutics to enhance their understanding of the doctor-patient relationship. Methods A newly developed and validated educational module on the “Doctor-patient relationship” was administered to 250 first-year undergraduate medical students at Kasturba Medical College Manipal. The session was structured into three key steps: Introduction Presenting Sir Luke Fildes’ famous painting, The Doctor. Self-understanding and interpretation Encouraging students to analyse and interpret the painting. Debriefing Facilitating discussions to consolidate learning. The session’s effectiveness was evaluated using the initial two levels of the Kirkpatrick evaluation model. The learners feedback regarding the usefulness of the session was captured using a validated questionnaire, while reflective writing assignments were used to explore students’ learnings from the intervention. Results Student feedback was overwhelmingly positive, with participants expressing that the session significantly enhanced their understanding of professional qualities and empathy in the doctor-patient relationship, rating their overall learning experience at 8.63 out of 10. Students expressed that the use of painting and interactive discussions greatly enriched their capacity to connect with emotional and ethical dimensions of medical practice. Reflective writing revealed the importance of building trust, demonstrating professional conduct, and maintaining empathy and compassion in clinical interactions. Conclusion Introducing a visual hermeneutics approach has the potential to cultivate empathy and foster a deeper understanding of the doctor-patient relationship. Introducing this approach during the formative years of medical training can nurture compassionate and virtuous conduct, reinforcing students’ commitment to delivering empathetic and competent care throughout their medical careers. Trial registration The institutional ethics committee approved the conduct of the study [IEC180/2023].